I've been working on this question but just can't crack it. It is as follows.

Using $ \frac {dy}{dx}= \frac {a\sqrt{x^2+y^2}+by}{bx}$ where $ y(1)=0 $

and by letting $ v=\frac{y}{x} $ transform the above differential equation to an equation in $v$ and $x$. Find the implicit solution of the resulting separable equation. Then use the relationship $y=xv$ to obtain $y+\sqrt{x^2+y^2}=x^{\frac{a}{b}+1}$

I've tried separate the upper terms into two fractions which makes the second term simply $\frac {by}{bx}=v$ but I am still left with the nasty square root with the y on the inside and I can't shift it easily to solve as a first order DE. Also I was thinking about solving it as a linear first order ODE but we have a squared term. Sorry about formatting as well, first time posting a question.


Just as you did $$\frac {dy}{dx}= \frac {a\sqrt{x^2+y^2}+by}{bx}$$ Let $$y=x v\implies y'=v+x v'$$ making the equation to be $$x v'=\frac ab \sqrt{1+v^2}$$ which is separable $$\int \frac{dx} x=\frac b a \int\frac{dv}{\sqrt{1+v^2}}$$ making $$\log(x)+C=\frac b a \sinh ^{-1}(v)$$ So $$v=\sinh\left(\frac ab \log(x)+C\right)\implies y=x \,\sinh\left(\frac ab \log(x)+C\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.